PEMBENTUKAN UNDANG-UNDANG DI INDONESIA DALAM PERSPEKTIF FIQH SIYASAH: INTEGRASI PRINSIP KEADILAN, KEMASLAHANTAN, DAN PARTISIPASI PUBLIK - Khalisatun Nurussa’adah; Akhmad Zaki Yamani (INTELIGENSIA MEDIA, 2025)
The formulation of laws is one of the fundamental pillars of Indonesia’s constitutional system, shaping public policy and the implementation of democratic principles. From the perspective of fiqh siyasah (Islamic political jurisprudence), lawmaking is not merely a political process but also a means to realize the values of justice (al-‘adl), public welfare (al-mashlahah), and public participation (musyarakah). This study aims to analyze the legislative process in Indonesia by examining the extent to which the principles of fiqh siyasah are integrated into the modern legislative system. The research employs a qualitative method with a normative and descriptive-comparative approach. Data were collected through literature studies on legislation, fiqh siyasah sources, and relevant academic documents. The findings reveal that Indonesia’s legislative process has partially accommodated the values of fiqh siyasah, particularly in aspects of social justice and public participation through mechanisms of public consultation and aspiration channels. However, the implementation of the principle of maslahah (public welfare) remains constrained by political interests and weak institutional coordination. Therefore, the integration of fiqh siyasah principles in lawmaking should be strengthened through an Islamic legal-ethical approach that emphasizes the moral responsibility of lawmakers toward public welfare.